Experimental studies on Friction stir processing of AZ31 Magnesium alloy. (2018) - Babu, J.; Anjaiah, M.; Mathew, Anoop
Abstract: Friction stir processing is a solid-state technique for microstructural modification using the heat from friction and stirring. The mechanical properties of friction stir processed AZ31 magnesium alloys can be improved due to the grain refinement of the microstructure which makes them suitable for Superplastic forming.The parameters of friction stir processing for AZ31 magnesium alloys are studied at the three different travelling speeds: 20, 30 and 40 mm/min with two different rotation speeds 600 and 800 rpm in the present investigation.Results reveal that the smallest precipitate size is obtained at spindle speed and feed rate combination of 800 rpm and 40mm/min. The corresponding Vickers hardness value is 63 which is around 50% higher than that of the base metal.